Pengaruh Efikasi Diri dan Motivasi Intrinsik terhadap Kinerja Karyawan pada PT. Bank X - Dahrul Siregar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
Each employee has different performance from one another, this is due to several factors including self-efficacy and intrinsic motivation, so this study aims to determine and partially analyze the effect of self-efficacy on performance and intrinsic motivation on performance and influence in a partial way. simultaneous self-efficacy and intrinsic motivation on the performance of the Marketing Division employees at PT. Bank X This type of research is an associative study, using a quantitative approach. The population in this study amounted to 60 people, so that all populations were sampled in this study. The data analysis technique in this study used multiple regression analysis. Based on the results of hypothesis testing, it can be concluded that partially there is a positive and significant influence between self-efficacy on employee performance in the marketing division, there is a positive and significant influence between intrinsic motivation on employee performance in the marketing division, there is a positive and significant influence between self-efficacy and intrinsic motivation of division employees marketing, there is an effect of self-efficacy, intrinsic motivation on employee performance simultaneously employees of the marketing division of PT. Bank X